Prophecy, cult and wilderness between Qumran and Revelation - Piazzolla, Francesco (Liber Annuus, 2024)
Abstract The article offers a comparison of two communities in time of crisis, Qumran and Revelation, through the study of a common language and corresponding images. In both groups, the same expressions are found speaking of the prophetic role in their respective communities and the same dynamics to counter dissidents and supporters of false prophecy. The common abandonment of the Temple liturgy leads both congregations to use an ethical meaning of the ancient rites, with a Christological nuance in the Churches of the Apocalypse. The desert, for the two groups, appears as the ideal place in which to live the experience of faith, under the attacks of the Devil, but protected by divine interventions.